(untitled) (Journal for Studies in Humanities and Social Sciences, 2020)
Customer service enhances the shopping experience of customers and impacts on their buying behaviour. Enhancing employees’ levels of psychological capital, general health and job satisfaction will likely impact positively on their satisfaction with life. The purpose of this study was to explore the impact of psychological capital, general health and job satisfaction on satisfaction with life of retail employees. A quantitative research design was used to collect the data on the biographical details, psychological capital, general health, job satisfaction and satisfaction with life of retail employees in Swakopmund, Walvis Bay and Windhoek, Namibia (n=453). A positive relationship was found between psychological capital, job satisfaction and satisfaction with life. General health reported a negative relationship with satisfaction with life. It is recommended that supervisors should encourage staff members to take on more challenging tasks, offer praise and recognition to employees that excel at their tasks and regularly assess job satisfaction levels in order to enhance satisfaction with life. In addition, organisations need to provide medical benefits to employees, encourage an active lifestyle or invite medical aid service providers to facilitate health seminars.